2011
DOI: 10.1364/ao.50.000901
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of a broadband dye laser using Pyrromethene and Rhodamine dyes

Abstract: A broadband dye laser pumped by a frequency-doubled Nd:YAG laser with a full-width half-maximum (FWHM) from 592 to 610 nm was created for the use in a dual-pump broadband CARS system called WIDECARS. The desired broadband dye laser was generated with a mixture of Pyrromethene dyes as an oscillator gain medium and a spectral selective optic in the oscillator cavity. A mixture of Rhodamine dyes were used in the amplifier dye cell. To create this laser a study was performed to characterize the spectral behavior o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…The moderate bandwidth mixture is Rhodamine 640 (R640) and Kiton Red 620 (KR620) dissolved in methanol, similar to that used in prior work, which provides broadband output centred near 607 nm, with a full width at half maximum (FWHM) of approximately 5-6 nm. The mixture providing broader bandwidth is a solution of Pyrromethene 597 (PM597) and Pyrromethene 650 (PM650), following the work of Tedder et al (2011). The mixture produces very broad output, covering a range of ∼570-610 nm.…”
Section: Picosecond Cars Diagnostic Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The moderate bandwidth mixture is Rhodamine 640 (R640) and Kiton Red 620 (KR620) dissolved in methanol, similar to that used in prior work, which provides broadband output centred near 607 nm, with a full width at half maximum (FWHM) of approximately 5-6 nm. The mixture providing broader bandwidth is a solution of Pyrromethene 597 (PM597) and Pyrromethene 650 (PM650), following the work of Tedder et al (2011). The mixture produces very broad output, covering a range of ∼570-610 nm.…”
Section: Picosecond Cars Diagnostic Systemmentioning
confidence: 99%
“…The present work, which is a follow-on to initial studies reported by Pendleton et al (2012), presents new CARS data on rotational temperature and vibrational distribution function (VDF) in nanosecond pulse discharges in nitrogen and air, both in a repetitively pulsed discharge in plane-toplane geometry and in a single-pulse discharge in point-topoint, diffuse filament geometry. By using a new broadband dye laser mixture (Tedder et al 2011), up to 20 vibrational levels could be probed, although only levels v = 0-9 were found to have populations above the detection limit. The experimental temporal evolution of rotational temperature and nitrogen VDF is compared to predictions of a coupled master equation/plasma chemistry kinetic model.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4 also shows the insertion of a variable angle of incidence transmission filter between the pre-amplifier and final amplifier. When used in combination with a very broad dye mixture [18], consisting of a solution of Pyrromethene 597 and Pyrromethene 650 dyes, this enables tuning of the broadband spectral output. Figure 5 shows the spectral output, as determined from the non-resonant background (NRB) spectrum of argon, along with the Stokes wavelengths for v = 0 to v = 10 transitions of N 2 , when a 552 nm edge dichroic filter is inserted oriented at an angle of 10° with respect to the laser beam propagation axis.…”
Section: Broadband Carsmentioning
confidence: 99%
“…The moderate bandwidth mixture is Rhodamine 640 (R640) and Kiton Red 620 (KR620) dissolved in methanol, similar to that used in prior work, which provides broadband output centered near 607 nm, with a full width at half maximum (FWHM) of approximately 5-6 nm. The mixture providing broader bandwidth is a solution of Pyrromethene 597 (PM597) and Pyrromethene 650 (PM650), following the work of Tedder et al (2011). The mixture produces very broad output, with a range covering from ~570-610 nm.…”
Section: B Picosecond Cars Diagnostic Systemmentioning
confidence: 99%
“…By using a new broadband dye laser mixture (Tedder 2011), up to 20 vibrational levels could be probed, although only levels v=0-9 were found to have populations above the detection limit. The experimental temporal evolution of rotational temperature and nitrogen VDF is compared to predictions of a coupled master equation / plasma chemistry kinetic model.…”
Section: Introductionmentioning
confidence: 99%